2019
DOI: 10.1111/saje.12224
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Foreign Agricultural Aid and Total Foreign Aid on Agricultural Output in African Countries: New Evidence from Panel Data Analysis

Abstract: Official Development Assistance may play an important role in increasing the resources to finance the agriculture sector and improve agricultural outcomes in African countries. Although this is a relevant issue, very few studies have investigated the link between foreign agricultural aid and national agricultural output. Using advanced econometrics techniques, this paper examines the impact of foreign agricultural aid and foreign aid on agriculture output in the panel data set of 29 African countries over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…They also find that aid appears to be less effective in countries with large fiscal deficits and high external debt. Instead of using general foreign aid as in Norton et al [ 37 ] and Kherallah et al [ 32 ], Barkat and Alsamara [ 6 ] use data for 29 African countries over the period of 1975–2013 to examine the impact of foreign agricultural aid and foreign aid on agricultural output. Their results show a small and positive impact of foreign agricultural aid and total foreign aid on agricultural output for low- and middle-income countries.…”
Section: Literaturementioning
confidence: 99%
“…They also find that aid appears to be less effective in countries with large fiscal deficits and high external debt. Instead of using general foreign aid as in Norton et al [ 37 ] and Kherallah et al [ 32 ], Barkat and Alsamara [ 6 ] use data for 29 African countries over the period of 1975–2013 to examine the impact of foreign agricultural aid and foreign aid on agricultural output. Their results show a small and positive impact of foreign agricultural aid and total foreign aid on agricultural output for low- and middle-income countries.…”
Section: Literaturementioning
confidence: 99%
“…Still, a study by Alabi (2014) investigated the impact of foreign agricultural aid on agricultural GDP and productivity in Sub-Saharan Africa (SSA) concluding that these aid had a positive impact more when are bilateral rather than multilateral. Work by Ssozi et al (2019), Barkat & Alsamara (2019) and Kornher et al (2021) also found positive relationships between aid and growth in agriculture. A positive growth-enhancer effect has been observed also in Kaya et al (2013), where foreign aid to agriculture reduces both directly and indirectly the poverty headcount ratio of recipient countries, a result that confirms the poorest welfareenhancing effect of aid to agriculture.…”
Section: Literature Reviewmentioning
confidence: 85%
“…Finally, we employ the most suitable estimation technique (augmented mean group (AMG)) (Eberhardt and Bond, 2009) that considers both heterogeneity and CSD. Traditional panel estimation methods such as DOLS and GMM are not suitable in the presence of heterogeneity and cross-sectional dependency and may lead to spurious results (Alsamara et al, 2018;Barkat and Alsamara, 2019). However, the AMG method allows for variation in the slope coefficients and error variance across countries, and deals with CDS (Eberhardt and Bond, 2009).…”
Section: Data and Empirical Methodologymentioning
confidence: 99%